HELICOBACTER PYLORI, TRANSMISSION, SYMPTOMS, DIAGNOSIS AND TREATMENT (ARTICLE REVIEW) - Essmaa Husssein Gutef (Web of Journals Publishing, 2024)
Helicobacter pylori is a type of bacteria that is grame-negative, microaerophilic, and has a helical shape (Figure .1). About half of the world's population typically has it in their stomachs. Those who are infected may develop chronic gastritis, which often remains symptomless in 85 percent of cases.